2006
DOI: 10.1111/j.1467-2494.2006.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the skin endogenous protective mitochondrial MnSOD byVitreoscilla filiformisextract

Abstract: Vitreoscilla filiformis (Vf), a filamentous bacteria living in fresh water is thought to contribute to the observed beneficial effects of Spa water on skin. An active fraction obtained from a Vf biomass was evaluated for its ability to modulate mRNA expression in cultured skin cells. cDNA array analysis was conducted first using a customized membrane including 1176 selected and fully identified genes involved in skin physiology and homeostasis then the newly developed full genome U133 plus 2.0 GeneChip from Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…PROPAGAPATH allowed us to identify this pathway for the first time in reconstructed skin, with a minimal number of steps when compared with the canonical myeloid differentiation primary response gene (88), nuclear factor kappa-light-chain-enhancer of activated B cells pathway. The VFB-derived LPS fraction stimulated gene expression and was inhibited with a PKCz inhibitor, suggesting that this specific fraction is indeed a key component of the protective action of VFB on skin, as has already been shown 4,5…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…PROPAGAPATH allowed us to identify this pathway for the first time in reconstructed skin, with a minimal number of steps when compared with the canonical myeloid differentiation primary response gene (88), nuclear factor kappa-light-chain-enhancer of activated B cells pathway. The VFB-derived LPS fraction stimulated gene expression and was inhibited with a PKCz inhibitor, suggesting that this specific fraction is indeed a key component of the protective action of VFB on skin, as has already been shown 4,5…”
Section: Discussionsupporting
confidence: 55%
“…Both in vitro and in vivo testing have shown that VFB stimulates endogenous anti-oxidant defenses in skin: in vitro, it stimulated mitochondrial superoxide dismutase 2 (SOD2) activity3 both at the mRNA and protein levels, while, in vivo, it decreased the number of ultraviolet-induced sunburn cells in human skin. VFB was thus proposed as an effective anti-aging ingredient for skin improvement and protection from endogenous and exogenous oxidative stress 3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquaphilus dolomiae is a non-spore forming bacterium belonging to the Neisseriaceae family, which is isolated from Avène thermal Water (France), historically used in the management of chronic inflammatory skin diseases. Similarly, the lysate of Vitreoscilla filiformis (VF) has been shown to enhance skin defence mechanisms (102) and to decrease UV-induced sunburn cells in human skin, possibly by the activation of cutaneous regulatory T cells (103). VF is a filamentous Gram-negative aerobic bacterium belonging to the Neisseriaceae family found in LaRoche-Posay thermal water, historically applied to manage chronic inflammatory skin diseases (103105).…”
Section: The Future Of Regenerative Surgerymentioning
confidence: 99%
“…These activities include: substance P antagonist (11), stimulation of skin anti-microbial peptide secretion, recovery of sunburn areas (12,13), activation of MnSOD as an inducible free-radical scavenger in keratinocytes for protecting cells against the uncontrolled production of reactive oxygen species (ROS) (14), modulation of mouse and human cutaneous inflammatory responses inducing interleukin (IL)-10 production in dendritic cells (DCs), and priming of regulatory T cells (15). It was shown that the activation of two independent TLR pathways occurs following DC stimulation with a V. filiformis lysate (13,15).…”
mentioning
confidence: 99%